임대인등의 실거주 갱신거절 사유의 정당성 판단 연구 - 뉴욕주 임대차안정화 법률 분쟁사례를 중심으로 - 김남근(Kim Namgeun) (법학연구, 2021)
개정 주택임대차보호법에 갱신요구 제도가 도입되자 임대차 갱신과 임 대료 인상을 둘러싼 분쟁이 크게 증가하였고, 사안 중에는 하급심 법원의 판례도 엇갈리는 등 임대차 현장에서 갱신제도를 둘러싼 혼선이 발생하 고 있다. 대표적인 사례가 임대인과 그 직계가족의 실거주를 이유로 갱신 거절을 하는 경우, 그 실거주의 진정한 의사, 진의(good faith)를 어디까지 인정할 수 있느냐에 관한 분쟁이다. 임대인등의 실거주 사유는 그 사유 자체가 아직 발생하지 아니한 장래의 사실에 관한 임대인의 주관적인 의 도를 내용으로 하고 있어서 임차인의 입장에서는 그 사유 발생 여부를 정 확하게 알기 어려운 사정이 있다. 임대인이 실거주하겠다고 주장하기만 하면 쉽게 갱신거절이 되는 경우, 임차인의 주거안정을 도모하기 위해 임 차인의 갱신요구권 제도를 도입한 개정 주택임대차보호법의 입법취지가 형해화될 수 있다. 그렇다고, 갱신거절의 통지 단계에서 임대인등의 실거 주를 뒷받침할 구체적인 사실관계나 그 진의를 명백하게 증명해야 한다 는 것도 무리이다. 신규 임대차의 전세가격이 급격히 인상되는 상황 속에 서 임차인이 분쟁을 기피하는 현상이 일반화되자, 임대인이 실거주를 이 유로 한 갱신거절을 임차인과의 협상용으로 남용하는 사례도 많아지고 있다. 그래서 개정 주택임대차보호법의 갱신제도와 유사한 제도를 오랜 기간 운영해 온 뉴욕주의 판례나 분쟁사례를 통해 그 정당성 판단기준을 연구하고자 하는 것이 이 논문의 주된 목적이다. 한편, 임대차 안정화 제도는 임대주택을 시장에 내놓아 임대료 수입을 목적으로 하는 경우에는 정당한 갱신거절 사유가 없는 한 계속 갱신을 허 용하되, 임대인등이 실주거로 사용할 사유가 명확한 경우에는 점유를 회 복하여 직접 사용할 수 있도록 하는 것이다. 이와 같은 방식으로 임차인 의 주거안정과 임대인의 소유권 행사의 균형을 맞출 수 있다. 실거주를 이유로 한 갱신거절 제도와 같은 안전장치가 있다면, 임차목적으로 시장 에 내놓은 임대차의 갱신횟수를 1회로 제한할 이유도 없다. 임대차 갱신 제도를 도입한 입법례 중에 그 갱신횟수를 1회로 제한하는 사례는 없다. “실거주”를 갱신거절이나 임대차 해지의 사유로 하는 입법례는 보편적이 지만, 이러한 입법례들은 계속적 갱신이나 기간을 정하지 않은 임대차를 전제하고 있다는 점을 주목해야 한다. 2022년 8월 개정 주택임대차보호법 에 의해 최초로 갱신된 임대차의 종료가 도래하기 전에 갱신요구권 행사 의 횟수를 더 늘리는 개정을 할 필요가 있다. When the renewal request system was introduced in the revised Housing Lease Protection Act, disputes over lease renewal and rent increase greatly increased. A typical case is the dispute over the extent to which the true intention and good faith of the landlord can be recognized when the landlord and his immediate family refuse to renew on the ground of their actual residence. The reason for the actual residence of the lessor, etc. contains the lessor's subjective intention regarding future facts that have not yet occurred, and it is difficult for the lessee to accurately determine whether the cause has occurred. If the landlord asserts that he/she wants to live, if the renewal is easily rejected, the legislative purpose of the revised Housing Lease Protection Act, which introduces the tenant's right to request renewal in order to promote the stability of the tenant's housing, may be jeopardized. However, it is unreasonable to have to clearly prove the truth or specific facts to support the real residence of the lessor, etc. in the notification stage of refusal of renewal. As the phenomenon of tenants avoiding disputes in the context of a rapid increase in the Jeonse price of new leases has become common, there are increasing cases in which lessors abuse their refusal to renew on the grounds of real residence for negotiation with lessees. Therefore, the main purpose of this thesis is to study the criteria for judging the legitimacy of New York State, which has operated a system similar to the renewal system of the revised Housing Lease Protection Act for a long time, through precedents and dispute cases. Under the rental stabilization law system, if a rental house is put on the market for the purpose of earning rent, renewal is continuously allowed unless there is a reasonable reason for non-renewal. In this way, it is possible to balance the stability of the tenant's housing with the landlord's ownership. There is no need to limit the number of renewals to one in lease put on the market for rental purposes if there is a safeguard such as non-renewal on the ground of primary residence. Among the legislative cases that introduced the lease renewal system, there is no nation where the number of renewals is limited to one. Legislative cases stating “primary residence” as grounds for non-renewal or termination of lease are common, but it should be noted that these legislative cases are premised on continuous renewal or lease with no fixed period. It is necessary to make an amendment to increase the number of the renewal request right before the end of the first renewed lease in August 2022. KCI Citation Count: 0